การลอยสินแร่ทองแดงรีแฟรคตอรี - อรรถพล สายคำตา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The study was conducted to determine the optimum of reagents used to process copper ore flotation under a laboratory scale. Moreover, this study was aimed to find out the ore sample properties in which they affect flotation by a study set of optical microscope, grain counting and Inductively Coupled Plasma Atomic Emission Spectrometry. Ore samples taken from Phu Kham copper-gold deposit, Lao PDR were used for this study. This deposit is considered as quite complicated ores. Results from the study of ore properties revealed that the composition of the ore samples contained pyrite, chalcopyrite and quartz at 24%, 5%, and 53% respectively. Grade of ore samples contained 1.87 - 2.50 % of Cu and 26 - 32 % of Fe. When size of ore grains was analyzed under microscope, it showed that the size range of liberation pyrite was -105+88 to -88+74 μm which is considered as optimal size for separating it from other minerals. Experimental studies of ore flotation were designed to study the chemical factors by types and dosages of reagent: frother collector and depressant reagent. The results showed that the most suitable condition of combination of factors gave percentage of copper recovery at 79.50 % and copper grade at 9.03 %. The suitable condition was as follows: - Frother reagent: PBM 604, dosages at 50 g/t (8.38 mg/l) - Collector reagent: Dithiophosphate, dosages at 50 g/t (8.38 mg/l) - Depressant reagent: Sodium-metabisulphite, dosages at 400 g/t (67.00 mg/l) Furthermore, the experimental studies were conducted to improve the efficiency of flotation after cleaning by the above method by cleaning it twice again. It was found that it increased copper grade 10.52% more than the above method did.